Analysis of phenazepam and 3‐hydroxyphenazepam in post‐mortem fluids and tissues. Issue 10 (5th April 2015) - Crichton, Megan L.; Shenton, Catriona F.; Drummond, Gail; Beer, Lewis J.; Seetohul, L. Nitin; Maskell, Peter D.
<x xml:space="preserve">Abstract</x> Phenazepam is a benzodiazepine that is predominantly used clinically in the former Soviet states but is being abused throughout the wider world. This study reports the tissue distribution and concentration of both phenazepam and 3‐hydroxyphenazepam in 29 cases quantitated by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) in a variety of post‐mortem fluids (subclavian blood, femoral blood, cardiac blood, urine, vitreous humour) and tissues (thalamus, liver and psoas muscle). In 27 cases, the cause of death was not directly related to phenazepam (preserved (fluoride/oxalate) femoral blood phenazepam concentrations 0.007 mg/L to 0.360 mg/L (median 0.097 mg/L). In two cases, phenazepam was either a contributing factor to, or the certified cause of death (preserved (fluoride/oxalate) femoral blood 0.97 mg/L and 1.64 mg/L). The analysis of phenazepam and 3‐hydroxyphenazepam in this study suggests that they are unlikely to be subject to large post‐mortem redistribution and that there is no direct correlation between tissues/fluid and femoral blood concentrations. Preliminary investigations of phenazepam stability comparing femoral blood phenazepam concentrations in paired preserved (2.5% fluoride/oxalate) and unpreserved blood show that unpreserved samples show on average a 14% lower concentration of phenazepam and we recommend that phenazepam quantitation is carried out using preserved samples wherever possible. Copyright © 2015 John Wiley & Sons, Ltd.